Silver Corrole Complexes: Unusual Oxidation States and Near‐IR‐Absorbing Dyes. Issue 48 (3rd October 2014) - Sinha, Woormileela; Sommer, Michael G.; Deibel , Naina; Ehret, Fabien; Sarkar, Biprajit; Kar, Sanjib
Abstract Macrocycles such as porphyrins and corroles have important functions in chemistry and biology, including light absorption for photosynthesis. Generation of near‐IR (NIR)‐absorbing dyes based on metal complexes of these macrocycles for mimicking natural photosynthesis still remains a challenging task. Herein, the syntheses of four new AgIII corrolato complexes with differently substituted corrolato ligands are presented. A combination of structural, electrochemical, UV/Vis/NIR‐EPR spectroelectrochemical, and DFT studies was used to decipher the geometric and electronic properties of these complexes in their various redox states. This combined approach established the neutral compounds as stable AgIII complexes, and the one‐electron reduced species of all the compounds as unusual, stable AgII complexes. The one‐electron oxidized forms of two of the complexes display absorptions in the NIR region, and thus they are rare examples of mononuclear complexes of corroles that absorb in the NIR region. The appearance of this NIR band, which has mixed intraligand charge transfer/intraligand character, is strongly dependent on the substituents of the corrole rings. Hence, the present work revolves round the design principles for the generation of corrole‐based NIR‐absorbing dyes and shows the potential of corroles for stabilizing unusual metal oxidation states. These findings thus further contribute to the generation of functional metal complexes based on such macrocyclic ligands.